Developing Robust Strategies for Climate Change and Other Risks A Water Utility Framework - Groves, David G. (RAND Corporation, 2014)
RAND researchers and collaborators present a comprehensive approach for water utilities to assess climate risks to their systems and evaluate adaptation strategies. The approach, based on Robust Decision Making, is demonstrated through pilot studies with two water utilities: Colorado Springs Utilities and New York City Department of Environmental Protection.